STUDY REGARDING THE IMPORTANCE OF EXERCISE IN PRIMARY SCHOOL CHILDREN - Alexandra Gabriela MILON; Adina Camelia ŞLICARU (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2017)
Exercise is very important for people, and especially for children, because they are still growing and developing. Exercise performed correctly since an early age helps the harmonious development of the body, strengthening one's health, learning motor skills correctly, developing/consolidating one's motor abilities. This paper focuses on children aged 7-10, because these ones are beginners and it is important for them to get used to exercise, in order for them to create a healthy lifestyle for themselves. Because of a lack of exercise, of time spent at school, because of tablet computers, computers, and television, children suffer from various disorders, such as: eye disorders, spine deformations, obesity, they cannot adapt to certain situations, they do not socialize, etc. This paper aims to highlight the importance of exercise as means of educating the children, but also as means of preventing certain disorders. Children who practice a sport socialize easier, are more organized, more attentive, have better focus, in short, they are more disciplined and healthier, physically and mentally.